2011
DOI: 10.5897/ajpp11.226
|View full text |Cite
|
Sign up to set email alerts
|

Protection of -tocopherol and selenium against acute effects of malathion on liver and kidney of rats

Abstract: Protection from effects of the organophosphate insecticide, malathion on the liver and kidney of male Wistar albino rats by -tocopherol and selenium was investigated. Significantly greater (P<0.01) mean concentrations of malondialdehyde (MDA) and lesser concentrations (P<0.01) of reduced glutathione (GSH) and tissues total proteins were observed in liver and kidney of rats exposed to malathion. Activities of the antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 74 publications
(59 reference statements)
4
41
1
Order By: Relevance
“…All at once, the two genes utilize a powerful anti-inflammatory action preventing the NF-κB pathway. 41 On the other hand, previous studies revealed that sele nium plays important roles in the enhancement of the antioxidant defense system, 42 increased GPx activity, 43 scavenge the free radicals and ROS 44 and down regulate the NF-κB pathway, 45 Consistent with previous study, SeNPs plays important roles in the enhancement of the antioxidant defense system whereas, the administration of SeNPs caused a marked improvement in hepatic antioxidant activities, which is due to its function in the active site of many antioxidant enzymes; like GPx. 46 selenium compounds or its metabolites may directly activate the Nrf2 pathway by modifying critical thiols in Keap1.…”
mentioning
confidence: 99%
“…All at once, the two genes utilize a powerful anti-inflammatory action preventing the NF-κB pathway. 41 On the other hand, previous studies revealed that sele nium plays important roles in the enhancement of the antioxidant defense system, 42 increased GPx activity, 43 scavenge the free radicals and ROS 44 and down regulate the NF-κB pathway, 45 Consistent with previous study, SeNPs plays important roles in the enhancement of the antioxidant defense system whereas, the administration of SeNPs caused a marked improvement in hepatic antioxidant activities, which is due to its function in the active site of many antioxidant enzymes; like GPx. 46 selenium compounds or its metabolites may directly activate the Nrf2 pathway by modifying critical thiols in Keap1.…”
mentioning
confidence: 99%
“…Significant decrease in total protein content was reported in liver and kidney tissues of malathion treated rats compared with the control group by Ozden et al (2009) andOthman (2011). Various oxidative stress parameters viz.…”
Section: Resultsmentioning
confidence: 99%
“…55 Se acts by scavenging the freeradicals and ROS. 56 This indicates that Se moderates oxidative stress-mediated complication. Moreover; Nanoparticles are designed to carry drugs and bring that medication all the way to the diseased cells in a body without harming the healthy cells.…”
Section: Discussionmentioning
confidence: 99%